Transformation of Scientific Reference Management: Mendeley Socialization for Magister Management Students at Tridinanti University - Dewi Rawani; Imam Akbar; Djatmiko Noviantoro; Sasiska Rani; Aida Rakhmawati; Tri Woro Setiati (Universitas Tridinanti, 2024)
The ability to manage scientific references systematically is one of the important skills for postgraduate students to support the preparation of quality scientific work. The socialization program for using Mendeley software is designed to improve the understanding and skills of Magister Management students at Tridinanti University in reference management. This activity involved 30 participants and was carried out through a structured approach, including theory sessions, direct practice and mentoring. The program results showed a significant increase in participants' understanding, from an average score of 2.1 to 4.1 (scale 1-5), as well as the success of 93% of participants in completing the final assignment correctly. Participants are able to utilize Mendeley's main features, such as library grouping, automatic citation, and compiling a bibliography in a predetermined format. Despite technical obstacles, such as unstable internet connections and incomplete reference metadata, the program was well received by participants, with 88% recommending this training for ongoing implementation. This training has proven effective in supporting students academic tasks and building a technology-based academic culture at Tridinanti University. For sustainability, integration of training into the regular curriculum and provision of follow-up sessions are proposed as strategic steps. This program is expected to improve the academic quality of students while supporting Tridinanti University's competitiveness at national and international levels.